PENGEMBANGAN MAJALAH SEKOLAH VIRTUAL UNTUK MENINGKATKAN LITERASI PESERTA DIDIK DI KOTA DEPOK - Refisa Ananda; Nunung Supratmi; Syafruddin Syafruddin (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
The school’s virtual magazine provide an opportunity for students to publish their writings. The development of virtual school magazines was carried out in 4 schools in Depok City, namely SMP and MA Madinatul Quran, SMK Bhakti Karya, and MTs. Al-Ittihad. This activity was carried out by utilizing the issues digital platform. The school's virtual magazine is published once a month. The school's virtual magazine is managed by the teacher and provided by the school as a forum for students' creativity. The writing rubrics provided in the virtual magazine are poetry, news, short stories, and photojournalism. Each school has 1 (one) issue account which is managed by the teacher as their virtual school magazine publishing platform for free.